The Molecular Structure and Morphology of Insoluble Coke in SAPO‐34 Catalyst. Issue 20 (11th July 2017) - Luo, Mingjian; Wang, Dakang; Hu, Bing; Fu, Yadong; Mao, Guoliang; Wang, Baohui
Abstract: The insoluble coke in SAPO‐34 catalyst is investigated by mass spectrometry and scanning electron microscopy (SEM). Results indicate the insoluble coke in SAPO‐34 catalyst is a reticulate structure composed of carbon‐chain bridged cycloalkanes and aromatics. This reticulate structure located near the surface of SAPO‐34 crystal. It is proposed that the continue alkylation and cyclization of cycloalkanes or aromatics with olefins is the main cause of the coke formation. Moreover, the coke preformed by olefins in downstream catalyst bed reduces the active region for methanol conversion. Abstract : The insoluble coke confined in SAPO‐34 cages is supposed to be a reticulate structure composed of carbon‐chain bridged cycloalkanes and aromatics. The coke is located near the surface of SAPO‐34 crystal and is formed via the continue alkylation and cyclization of cycloalkanes or aromatics with olefins.